Practical application of history taking in patient care among nurses of Central Province, Sri Lanka - Rathnayake, A.; Bandara, O.; Mudalige, U. (University of Jaffna, 2024)
The primary goal of nursing care is to meet the physical, psychological, and spiritual needs of individuals. History taking, as the initial step in nursing assessment, should focus on addressing the patient's physical and biopsychosocial needs. However, many patients report that their concerns are not adequately addressed during hospital stays. This highlights the importance of exploring practical approaches to improve nursing history taking. The aim of the study is to explore the perception, barriers and practical approaches in history-taking in patient care among nurses working in the central province, Sri Lanka. Ethical clearance was granted by the Faculty of Allied Health Sciences, University of Peradeniya. Eight focus group discussions were held with 40 nurses from four government hospitals in the Central Province of Sri Lanka, between May and August 2024. A purposive sampling technique was used, and qualitative thematic analysis was carried out by two independent researchers. The main 04 themes and 11 subthemes were obtained from qualitative thematic analysis. (Main theme 1: Effective initial approach in history taking: Diversity of history taking from admission to discharge, Initial one minute to explode, Focus on needs of patients) (Main theme 2: Approach of inquiry directs the interview: Impact of Pattern of questioning, Impact of Tone of questioning, Explore Possible questions) (Main theme 3: Untold stories are important: Identification of Non-verbal clues, Investigate indirect Questions) (Main theme 4: Challenges to address: Unfavourable clinical environment, Haphazard history taking, Unfavourable Patient factors of history taking). Nurses' participation in history-taking within clinical settings is vital for creating an effective nursing care plan. However, the practical aspects of history-taking can be challenging, as its success relies on patient-related factors, environmental conditions, and the healthcare provider. The role of nurses in using the biopsychosocial approach during history taking is crucial for providing comprehensive nursing care. Addressing the challenges associated with history taking requires ongoing professional development.
Keywords: History taking; Nursing assessment; Biopsychosocial approach